Lexical Import And Media Integration: How Russian Media Naturalize Loanwords - Ernst Ashotovich Petrosyants (American Journal Of Social Sciences And Humanity Research, 2025)
This article investigates how Russian media contribute to the diffusion and nativization of loanwords, combining contact-linguistic theory with a multimodal corpus approach. Building on foundational accounts of borrowing and replication and on a typology of anglicisms, the study constructs a multimodal micro-corpus of media instances (print, web, podcast, and video), applies an iterative codebook and a staged coding regime (first-cycle attribute/ descriptive/in vivo codes → second-cycle focused/pattern coding), and triangulates qualitative case analysis with basic quantitative indicators (frequency, dispersion, morphosyntactic integration). Empirical case studies (e.g. the Spanish-derived “окупас” and the anglicism “триггер”) demonstrate a recurrent lifecycle: (1) introduction with glossing and source attribution in high-prestige press; (2) narrative normalization in long-form audio; and (3) de-glossing and productive derivation in high-reach visual/multimodal genres. The media’s multimodal affordances (captions, imagery, prosody) accelerate both pragmatic uptake and morphological productivity. The article argues that media act as active agents of lexical replication—filling referential gaps and negotiating prestige—rather than passive transmitters of foreign items. Practical implications for corpus methodology, lexicography and media language policy are discussed.